Teacher Performance Management Model Based on the Merdeka Mengajar Platform: A Study of Primary Schools in Blang Cut Pidie District. - Isnabet, Isnabet; Najmuddin , Najmuddin; Bahri, Saiful (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study seeks to evaluate the teacher performance management methodology based on the Merdeka Mengajar Platform at State Elementary School Blang Cut, Mila Subdistrict, Pidie Regency. This research utilizes a qualitative methodology to thoroughly examine the application of the Merdeka Mengajar Platform throughout the teacher performance management cycle, encompassing planning, implementation, organization, and control. Data were gathered via interviews with the principal and instructors, with observations of the Merdeka Mengajar Platform's usage and examination of documentation. The research findings aim to elucidate the advantages, obstacles, and facilitating and impeding elements within the performance management model derived from the Merdeka Mengajar Platform at State Elementary School Blang Cut. This research identifies the Merdeka Mengajar Platform's potential to enhance performance administration efficiency, facilitate teacher self-reflection, and support ongoing competency development. This research seeks to ascertain the impact of the Principal's Planning, Implementation, Organization, and Control, as informed by the Merdeka Mengajar Platform, on enhancing teacher performance at State Elementary School Blang Cut, Mila Subdistrict, Pidie Regency.